Threshold Effects of the Network Structure in the Relationship Between Patent PageRank and Patent Value - Ke-Chiun Chang; Yen-Lin Li; Ting Zhang; Xingxing Xiang; Kuang-Cheng Chai (IEEE Access, 2020)
This study employed the panel threshold regression model to test whether the network structure of the patent citation network has a threshold effect on the relationship between patent PageRank and patent value. The results demonstrate that the network structure has a threshold effect on the relationship between patent PageRank and patent value, and there is an optimal interval in the network structure. In the optimal interval, the positive impact of patent PageRank and patent value is at the highest level. Hence, the relationship between patent PageRank and patent value is non-linear.